Deixis in English and Buginese - Ashariah Chairul Nusu (Hasanuddin University, 2018)
The phenomenon of deixis is the most obvious way to describe the relationship between language and context within the structure of the language itself. The aims of the research were to observe the type of location deixis used in English and Buginese and to explain their differences by using Stephen C. Levinson’s Theory. The research employed a descriptive qualitative method, conducted in Barebbo Sub-district, Bone Regency. The Buginese data were collected from note-taking and recording, and English data were from internet. The result of this research indicated that deixis in English and Buginese were used in certain context. They were different especially in English which used 4 types of location to indicate something in a conversation between two or more people. Buginese used 9 different words based on distance of the speaker, hearer and object. Difference of location Deixis in English and Buginese were influenced by the culture and different way of wording in language.